Characterising and the perception of the burden of family caregivers for people suffering chronic disease in Arauca (Orinoquia, 2015)
A group of family caregivers caring for people suffering from non-transmissible chronic diseases (NTCD) attending the San Vicente Hospital in Arauca was characterised and their perception regarding the level of care burden was determined by using a cross-sectional, quantitative, descriptive study involving intentional, non-probabilistic sampling of 42 family caregivers of people suffering NTCD, capturing spatial data concerning them between August and October 2012. This study forms part of the Reducing Chronic Disease Burden Programme in Colombia.The description of the socio-demographic characteristics and health data regarding the family caregivers of people suffering NTCD and those receiving their care attending San Vicente Hospital in Arauca led to an approach being made to assessing their care conditions. Regarding perception of care burden level, 83% of the family caregivers considered that they were not overburdened, 7% were slightly overburdened and 10% were intensely overburdened.Key words: Caregiver;  disease cost; chronic disease (Decs).
Keywords: Caregiver; disease cost; chronic disease (Decs).